Makna Al-Qurán Secara Umum dan Kedudukannya sebagai Sumber Ilmu Pengetahuan - Hidayatulloh, M. Deni (CV Kalimasada Group, 2023)
This paper discusses the meaning of the Qur'an, both in terms of language and terminology. Many scholars have different views on its definition. It also discusses the position of the Qur'an as a science. This paper is a library research, by collecting related literature, then presented in a descriptive qualitative manner, namely presenting the data as it is. Based on the words of Allah SWT accompanied by asbabu nuzulnya about the verse. The Qur'an was revealed as a guide to realize the mission of Islam, which is rahmatan lil aalamin. In this case, it is the duty of humans to observe, examine, search and explore the values contained in the Qur'an. There are many verses of the Qur'an that give hints about science and even technology, however, this position is still not widely realized by Muslims themselves. If these signs can be uncovered, then it can be a strengthening of the faith of Muslims and even become an effective means of broadcasting Islam. However, this position is still not widely realized by Muslims themselves. If these signs can be uncovered, they can strengthen the faith of Muslims and even become an effective means of propagating Islam.